Assessment Of Demand For Recreational Sports Personnel In Baturraden Tourism Area Banyumas - Gita Ramadhan; Nargiza Pirimova; Hussein Ali Faqier (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to identify the composition and needs of recreational sports personnel in Lokawisata Baturraden to support service quality and operational safety in recreational facilities. Methodology: This research applied a descriptive qualitative method using the Miles and Huberman model for data analysis. Data were collected through observation, interviews, documentation, and literature review. Tools included structured interview guides and dichotomous questionnaires analyzed manually. Main Findings: There were 17 recreational sports personnel managing four main facilities: slide pool, paddle boat, flying fox, and water boom. Only flying fox personnel held relevant certificates. Other facilities lacked certified or appropriately gender-diverse staff. Female personnel were notably absent where needed for safety and visitor support. Educational qualifications were mostly limited to senior high school. Novelty/Originality of this study: This study provides a practical workforce needs analysis for recreational sports tourism in a natural tourism setting. It identifies competency gaps and safety risks, offering recommendations for recruitment and certification strategies to improve visitor service and safety in recreational destinations.